Validation of the Behavioural Observation Scale 3 for the evaluation of pain in adults. (27th April 2017) - Frasca, M.; Burucoa, B.; Domecq, S.; Robinson, N.; Dousset, V.; Cadenne, M.; Sztark, F.; Floccia, M.
Abstract: Background: Many behavioural scales are available to assess pain but none are suitable for a quick evaluation of non‐sedated and non‐geriatric adults. The Behavioural Observation Scale 3 (BOS‐3) is short, composed of five items. This study examined its feasibility and diagnostic performances. Methods: Adult patients were included from medical and surgical departments of the University Hospital of Bordeaux. In a cross‐sectional study, BOS‐3 was compared to Numerical Rate Scale (NRS) with communicating patients (CP) and Behavioural Scale for the Elderly Person (ECPA2) with non‐communicating patients (NCP). Each time, BOS‐3 and reference scale were performed by an internal caregiver and an external expert. Results: We included 447 patients: 395 communicating and 52 non‐communicating. All patients were assessed by the BOS‐3 and the reference test. All BOS‐3 were carried out in less than one minute with only four missing data. Its reproducibility (ICC = 0.77 [95% CI 0.73–0.81] with CP and 0.93 [95% CI 0.89–0.97] with NCP) and its internal consistency (Cronbach α = 0.67 with CP and 0.70 with NCP) were good. In non‐communicating patients, ROC analysis set a threshold at 3 on 10. Sensitivity was 0.87 [95% CI 0.77–0.96], specificity 0.97 [95% CI 0.93–1.00], positive predictive value 0.93 [95% CI 0.86–0.99] and negative predictive value 0.95 [95% CI 0.89–1.00]. In communicating patients, sensitivity decreased to 0.34 [95% CI 0.28–0.38] but specificity reached 0.96 [95% CI 0.94–0.98] and positive predictive value 0.75 [95% CI 0.70–0.79]. Conclusions: BOS‐3 had good metrological properties in non‐communicating adults. With communicating patients, a positive BOS‐3 could be an additional tool to confirm pain, when underestimated on the NRS. Significance: This study describes the diagnostic performances of a behavioral pain assessment scale designed for non‐geriatric and non‐sedated adults. The results show its validity in non‐communicating patients and suggest its usefulness as an ancillary tool in communicating patients in whom simple numerical scales are often insufficient.